Prognostic Significance of Flow Cytometric Immunophenotyping in Patients with Acute Myeloid Leukemia - Demircioglu, Sinan; Ekinci, Omer; Dogan, Ali; Ulas, Turgay (Galenos Publ House, 2022)
Objective: Chromosomal abnormalities are one of the most important prognostic factors in acute myeloid leukemia (AML). However, not all patients may have such informative chromosomal abnormalities. Although there are many studies on the prognostic value of immunophenotyping in AML, it is still not used as a prognostic marker. In this study, we aimed to investigate the effects of CD13, CD33, CD34, CD117, MPO and HLADR expressions on prognosis of non-acute promyelocytic leukemia AML.Methods: One hundred thirteen patients diagnosed as having non -acute promyelocytic leukemia AML and followed up between 2010 and 2018 were included in this study. The associations of CD13, CD33, CD34, CD117, MPO and HLA DR expressions with chemotherapy response, progression free survival (PFS) and overall survival (OS) were statistically analyzed.Results: It was seen that response to chemotherapy was achieved in 67.3% of the patients. Median PFS duration was 9 months and median OS duration was found as 13 months. Of the immunophenotypic characteristics, only MPO expression was determined to be an independent risk factor for PFS and OS.Conclusion: Immunophenotypic features may be helpful in the diagnosis of AML as well as give an idea about prognosis. In this study, MPO expression was shown to be an independent risk factor for PFS and OS in our own patient population.
Keywords: Acute myeloid leukemia; immunophenotyping; prognosis; survival